2015
DOI: 10.1002/adem.201400448
|View full text |Cite
|
Sign up to set email alerts
|

Micro‐Forming Using Ultrafine‐Grained Aluminum Processed by Equal‐Channel Angular Pressing

Abstract: A very high-purity (99.999%) aluminum was processed by equal-channel angular pressing (ECAP) at room temperature through 1 to 8 passes using a die with a channel angle of 90°. Analysis shows that processing by ECAP produces an ultrafine-grained (UFG) structure with a grain size of %1.3 mm and with microhardness and microstructural homogeneity. The mechanical properties and the fracture behavior were evaluated using micro-tensile testing after ECAP processing. A micro-forming process was used to fabricate a mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 52 publications
(51 reference statements)
0
14
0
Order By: Relevance
“…Imposing a short term anneal of 10 minutes after the HPT processing has a significant effect on the microstructure and tensile properties of the HPT-processed specimens. There exists an optimum condition for the Al-1% Mg alloy by processing using HPT at room temperature and then giving the material a short anneal for 10 minutes at 423 K. Pure aluminium processed by ECAP to 8 passes produced materials with an average grain size of 1.3 m and this has been successfully applied to micro-forming of micro-turbine parts [17,18]. It was 07002-p. 5 reported that the geometries and surface quality of the compressed samples can be improved using UFG pure Al processed by ECAP through 8 passes by comparison with coarse-grained pure Al [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Imposing a short term anneal of 10 minutes after the HPT processing has a significant effect on the microstructure and tensile properties of the HPT-processed specimens. There exists an optimum condition for the Al-1% Mg alloy by processing using HPT at room temperature and then giving the material a short anneal for 10 minutes at 423 K. Pure aluminium processed by ECAP to 8 passes produced materials with an average grain size of 1.3 m and this has been successfully applied to micro-forming of micro-turbine parts [17,18]. It was 07002-p. 5 reported that the geometries and surface quality of the compressed samples can be improved using UFG pure Al processed by ECAP through 8 passes by comparison with coarse-grained pure Al [18].…”
Section: Discussionmentioning
confidence: 99%
“…There is only limited research on the application of SPD processed materials in micro-forming [6,[15][16][17][18]. Therefore, experiments were conducted to investigate HPT processing of an Al-1% Mg alloy and to develop a processing route to improve the material ductility after SPD processing in order to attain a material suitable for micro-forming applications.…”
Section: Introductionmentioning
confidence: 99%
“…For these experiments, the billets were sprayed with an MoS 2 lubricant and processed for 1, 2, 4 and 8 passes. Further details on ECAP processing are provided elsewhere [14].…”
Section: Experimental Materials and Parametersmentioning
confidence: 99%
“…The UFG pure Al has been successfully applied to fabricate micro-turbine using micro-forming at room temperature [27]. The UFG AZ31 alloy processed by HPT through 5 turns with an average grain size of 200 nm has excellent formability during micro-embossing using the V-groove die.…”
Section: Matec Web Of Conferencesmentioning
confidence: 99%